Economic analysis of empiric versus diagnostic-driven strategies for immunocompromised patients with suspected fungal infections in the People's Republic of China - Mao NY; Lesher B; Liu QF; Qin L; Chen YX; Gao X; Earnshaw SR; McDade CL; Charbonneau C (Dove Medical Press, 2016)
Ningying Mao,1 Beth Lesher,2 Qifa Liu,3 Lei Qin,2 Yixi Chen,4 Xin Gao,2 Stephanie R Earnshaw,5 Cheryl L McDade,5 Claudie Charbonneau,61School of International Pharmaceutical Business, China Pharmaceutical University, Nanjing, People's Republic of China; 2Pharmerit International, Bethesda, MD, USA; 3Hematology Department, Nanfang Hospital, Southern Medical University, Guangzhou, 4Pfizer Investment Co. Ltd., Beijing, People's Republic of China; 5RTI Health Solutions, Research Triangle Park, NC, USA; 6Pfizer International Operations, Paris, France Abstract: Invasive fungal infections (IFIs) require rapid diagnosis and treatment. A decision-analytic model was used to estimate total costs and survival associated with a diagnostic-driven (DD) or an empiric treatment approach in neutropenic patients with hematological malignancies receiving chemotherapy or autologous/allogeneic stem cell transplants in Shanghai, Beijing, Chengdu, and Guangzhou, the People's Republic of China. Treatment initiation for the empiric approach occurred after clinical suspicion of an IFI; treatment initiation for the DD approach occurred after clinical suspicion and a positive IFI diagnostic test result. Model inputs were obtained from the literature; treatment patterns and resource use were based on clinical opinion. Total costs were lower for the DD versus the empiric approach in Shanghai (¥3,232 vs ¥4,331), Beijing (¥3,894 vs ¥4,864), Chengdu, (¥4,632 vs ¥5,795), and Guangzhou (¥8,489 vs ¥9,795). Antifungal administration was lower using the DD (5.7%) than empiric (9.8%) approach, with similar survival rates. Results from one-way and probabilistic sensitivity analyses were most sensitive to changes in diagnostic test sensitivity and IFI incidence; the DD approach dominated the empiric approach in 88% of scenarios. These results suggest that a DD compared to an empiric treatment approach in the People’s Republic of China may be cost saving, with similar overall survival in immunocompromised patients with suspected IFIs. Keywords: aspergillosis, cost-effectiveness analysis, voriconazole, caspofungin, itraconazole